1973
DOI: 10.1128/aac.3.2.270
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Chemotherapeutic and Pharmacodynamic Activities of Cephradine, Cephalothin, and Cephaloridine in Mice

Abstract: Cephradine, a new semisynthetic cephalosporin derivative, is 7[D(-)-2-amino-2-(1 ,4-cyclohexadien-1-yl)acetamido]-3-methyl-8-oxo-5-thia-1-azabicyclo[4.2.0]oct-2-ene-2-carboxylic acid hydrate. The compound has a broad spectrum of antimicrobial activity in vitro. When given subcutaneously to mice, cephradine was appreciably more effective than cephalothin against infections induced by penicillinase-producing Staphylococcus, Escherichia coli, Klebsiella pneumoniae, or Enterobacter cloacae strains. Cephradine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1974
1974
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…This was reflected by the presence of a biologically active metabolite in the urine of mice treated with cephacetrile, cephapirin, or cephalothin. The serum values obtained in mice with cephalothin, cephaloridine, and cephapirin are in general agreement with those reported by other investigators (3,17). Wick and Preston have reported generally lower values for cefazolin, cephalothin, cephaloridine, and cephanone in mice (22).…”
Section: Resultssupporting
confidence: 82%
“…This was reflected by the presence of a biologically active metabolite in the urine of mice treated with cephacetrile, cephapirin, or cephalothin. The serum values obtained in mice with cephalothin, cephaloridine, and cephapirin are in general agreement with those reported by other investigators (3,17). Wick and Preston have reported generally lower values for cefazolin, cephalothin, cephaloridine, and cephanone in mice (22).…”
Section: Resultssupporting
confidence: 82%
“…10 times the MIC, a maximal bactericidal rate is achieved (7). The killing-curves were roughly similar (0-5h) at all concentrations for all 3 (10,20). cephalosporins.…”
Section: Discussionmentioning
confidence: 77%
“…The difference in effect in vivo in spite of similar MICs for the three cephalosporins could be due to various factors concerning antibiotic activity in vitro or in vivo, such as early bactericidal activity (2,16,20), post-antibiotic effect (12,27), protein binding (1,5,18), or pharmacokinetic properties The determination of the MIC or MBC does not reveal the early bactericidal potential of the antibiotic. For this purpose, time-kill curves are necessary (16).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolism and Excretion-A study in mice and dogs using paper chromatographic techniques showed that no metabolites of cephradine could be found in the urine (71,73). A study in humans also could not find any metabolites of cephradine (63).…”
Section: The Value Of Vds Shown Inmentioning
confidence: 99%